Flatfish fishery off Cochin and some aspects of the biology and stock of Malabar sole Cynoglossus macrostomus (Norman) - Nair, Rekha J (Indian Journal of Fisheries, 2011)
Flatfish landings increased from an estimated 58 t in 2000 to 299 t in 2002, butdeclined to 65 t in 2003 and 61 t in 2004 at Cochin. August and September werethe months of peak landings, which were also the peak spawning months. Theoptimum length of exploitation was 124 mm. Annual growth coefficient (K) andLô€ƒ were 0.79 and 212.5 mm respectively. The resource is being exploited at alevel (E = 0.78) higher than the optimum (Emax = 0.458). Appropriatemanagement measures are discussed.